New zeolite-like RUB-5 and its related hydrous layer silicate RUB-6 structurally characterized by electron microscopy. (2020) - Krysiak, Yas¸ar; Marler, Bernd; Barton, Bastian; Plana-Ruiz, Sergi; Gies, Hermann; Neder, Reinhard B.; Kolb, Ute
No abstract available